Comparison Of Outcomes Between Early And Delayed Reduction Of Nasal Bone Fractures - Kousar, Amna; Chaudhry, Sadia; Masood, Sundas; Akram, Ansa Umara; Javaid, Amna; Piracha, Adia Bushra (Journal of Rawalpindi Medical College, 2024)
Objective: To determine the outcomes of early versus delayed reduction of nasal bone fractures in terms of patient satisfaction and postoperative pain. Study Design: Comparative study. Study Setting & Duration: Department of Otorhinolaryngology, at Rawalpindi Teaching Hospital, Rawalpindi. The duration of the study was 6 months after approval by the Ethical Committee from February 2023 to July 2023. Materials and Methods: A total of 96 patients were selected. The study participants were individuals who, according to operational definitions, had nasal bone fractures and presented for evaluation at the Department of Otorhinolaryngology, Head & Neck Surgery at Rawalpindi Teaching Hospital, Rawalpindi. Patients were divided into two groups. Patients who underwent early reduction (within 2 weeks of trauma) were included in Group A while those who underwent delayed reduction (more than 2 weeks) were included in Group B. They also met all inclusion and exclusion criteria requirements and these requirements were strictly adhered to to control confounders and bias. Patients were chosen via a series of non-probability sampling. SPSS 28 was used to determine the frequencies in the data. Results: A total of 96 patients were included in this study. Out of which 52(54.17 %) were males and 44(45.8 %) were females. Patients who underwent early reduction had higher mean satisfaction scores on the seventh and fourteenth postoperative day (4.22 ± 0.75 and 4.60 ± 0.49 respectively) than those who underwent Delayed reduction (2.41± 0.82 and 2.93 ± 0.80 respectively). Patients who underwent early reduction had a better mean Pain Intensity score at 0(2.37 ± 0.81)3rd (1.37 ± 0.81), and 7th-day (0.58 ± 0.49) than the Delayed reduction, at 0(5.83 ± 1.20), 3rd (5.08 ± 0.67), and 7th-day (4.31 ± 0.58). Patient discomfort was more intense in the delayed reduction group than in the early reduction group. Early reduction led to higher patient satisfaction and a better mean pain intensity score. Conclusion: The results of nasal fractures between the early and delayed reduction groups did differ statistically significantly. Early reduction decreased pain intensity and increased patient satisfaction. Keywords: early reduction, delayed reduction, nasal bone fractures, Nasal bone.